Pengaruh Edukasi Protokol Kesehatan Covid-19 Terhadap Perilaku Santri, Guru dan Karyawan Pondok Pesantren Baron - Karnoto Abdul Aziz; Katmini (Politeknik Negeri Jember, 2022)
Knowledge and negative behaviors towards health protocols (washing hands, wearing masks, maintaining distance) as an effort to prevent Covid-19 in the scope of boarding schools are the main factors causing the number of Covid-19 incidents to continue to occur and increase, so there needs to be educated about health protocols (washing hands, wearing masks and maintaining distance) so that the public can avoid Covid-19 and prevent the occurrence of Covid-19 transmission. The purpose of the study is to analyze the effectiveness of health protocol education to improve the knowledge and behavior of students, teachers and employees of Islamic Boarding School Baron East Java. Desain pre-experimental research pretest-postest with control group design. The sample was divided into case and control groups of 55 and 49 respondents, respectively. Sampling techniques are used proportional random sampling. Independent variables of health education protocol, dependent variables of knowledge and behavior. The instruments used in the study are behaviour questionnaires conducted for validity and reliability tests. The results showed that therewere differences in the level of knowledge of students, teachers and employees after being given health protocol education (p = 0.001), and there were differences in the behavior of students, teachers, and employees after being given health protocol education (p = 0.000). Education has a major impact on-improving knowledge and behaviour about health protocols. The hope is that with good knowledge and positive behavior can reduce the rate of Covid-19 transmission within the scope of boarding schools. The study hopes that the results of this study can be a source of information about increasing knowledge and behavior about health protocols.